Den måske afsindige, måske ondsindede Lene Andersdatter : En dårekistesag fra Sjællands stiftsøvrighedsarkiv - Christiansen, Benjamin Brandt (Kirkehistoriske Samlinger, 2025)
These transcribed sources concern Lene Andersdatter, a woman living in the Danish town of Helsingør during the 1760s. The original seven documents behind the transcription are all from the archives of the diocesan authority (stiftsøvrighed), i.e. the bishop and the diocesan governor. They consist of letters from diocesan authority copybooks and extracts from local police court protocols. As a whole, the sources describe Lene Andersdatter’s confrontations with neighbours and authorities, and their subsequent responses to these confrontations. After a violent episode in 1762, the town magistrate placed Lene in a hospital confinement cell. Owing to a positive attestation from her pastor, she was quickly released and apparently had no interaction with the authorities for two years. In 1764, however, Lene acted violently again and was once more confined at the hospital. Finding her behaviour there unacceptable, the authorities obtained a royal resolution and transferred Lene to a workhouse. In the article around the transcription, the sources are contextualized in terms of institutions and relevant legal sections of the Danish Code of 1683, and it is argued that separating unpunishable insanity from punishable malice was a central theme throughout Lene’s case.